2010
DOI: 10.1016/j.freeradbiomed.2009.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Total body irradiation causes residual bone marrow injury by induction of persistent oxidative stress in murine hematopoietic stem cells

Abstract: Ionizing radiation (IR) and/or chemotherapy cause not only acute tissue damage but also late effects including long-term (or residual) bone marrow (BM) injury. The induction of residual BM injury is primarily attributable to the induction of hematopoietic stem cell (HSC) senescence. However, neither the molecular mechanisms by which IR and/or chemotherapy induce HSC senescence have been clearly defined, nor has an effective treatment been developed to ameliorate the injury. Thus, they were investigated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
255
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(273 citation statements)
references
References 45 publications
17
255
1
Order By: Relevance
“…A radiation-induced increase in ROS generation and/or an oxidative stress has been observed in vivo (21). Our results reveal that both DUOX1 and its maturation factor DUOXA1 are up-regulated several days after irradiation in human thyrocytes, supporting the role of DUOX1-based NADPH oxidase in a chronic oxidative stress.…”
Section: Discussionsupporting
confidence: 69%
“…A radiation-induced increase in ROS generation and/or an oxidative stress has been observed in vivo (21). Our results reveal that both DUOX1 and its maturation factor DUOXA1 are up-regulated several days after irradiation in human thyrocytes, supporting the role of DUOX1-based NADPH oxidase in a chronic oxidative stress.…”
Section: Discussionsupporting
confidence: 69%
“…Increased production of ROS in association with HSC defect has been observed in several other pathological conditions, such as deletion of Bmi1 (127, 136), MDM2 (1) and TSC1 (23), Fanconi anemia mutation (38), and aging (68). Similarly, we showed that exposure of mice to a sublethal dose of TBI induced a persistent increase in ROS production in HSCs (157). The induction of chronic oxidative stress was associated with sustained increases in oxidative DNA damage in HSCs, inhibition of HSC clonogenic function, and induction of HSC senescence (32, 90, 157).…”
Section: Reactive Oxygen Speciessupporting
confidence: 77%
“…Also, NOX4, localized in the perinuclear space was also the source of nuclear superoxide generation in hepatocytes (38). Interestingly, exposure of mice to ionizing radiation increased the expression of NOX4 in hematopoietic stem cells (10,39). The inhibition of NOX in the ionizing radiation-treated mice, attenuated the ROS and DNA damage associated with the ionizing radiation (40).…”
Section: Discussionmentioning
confidence: 99%